2016
DOI: 10.1007/s11357-016-9922-1
|View full text |Cite
|
Sign up to set email alerts
|

Cristacarpin promotes ER stress-mediated ROS generation leading to premature senescence by activation of p21waf-1

Abstract: Stress-induced premature senescence (SIPS) is quite similar to replicative senescence that is committed by cells exposed to various stress conditions viz. ultraviolet radiation (DNA damage), hydrogen peroxide (oxidative stress), chemotherapeutic agents (cytotoxic threat), etc. Here, we report that cristacarpin, a natural product obtained from the stem bark of Erythrina suberosa, promotes endoplasmic reticulum (ER) stress, leading to sub-lethal reactive oxygen species (ROS) generation and which eventually termi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
20
0
1

Year Published

2017
2017
2022
2022

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 23 publications
(22 citation statements)
references
References 43 publications
1
20
0
1
Order By: Relevance
“…High-LET radiation can induce higher ROS levels in vivo and in vitro compared with low-LET radiation (Datta et al, 2012). High levels of ROS are often related to compact heterochromatin (HC; Chakraborty et al, 2016;Tada et al, 2004). HC prevents γH2AX foci expansion and DSB repair, and the latter is relieved by ATM-dependent KAP-1 phosphorylation (Brunton et al, 2011).…”
Section: Discussionmentioning
confidence: 99%
“…High-LET radiation can induce higher ROS levels in vivo and in vitro compared with low-LET radiation (Datta et al, 2012). High levels of ROS are often related to compact heterochromatin (HC; Chakraborty et al, 2016;Tada et al, 2004). HC prevents γH2AX foci expansion and DSB repair, and the latter is relieved by ATM-dependent KAP-1 phosphorylation (Brunton et al, 2011).…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, a work on cristacarpin, a prenylated pterocarpan found in E. suberosa bark, confirmed that both PANC-1 (human pancreatic cancer cells) and MCF-7 cells were sensitive to this compound. Indeed, cell viability was decreased without toxic effects on non-cancer cell lines, such as HUVEC (human endothelial cells) and BPH-1 cells (human benign prostatic hyperplasia cells) [36]. In addition, the authors showed that cristacarpin, in an in vivo experiment with a 4T1 allograft mouse mammary carcinoma model, could prevent tumor growth by inducing premature senescence through both G1 phase blocking and ROS-dependent activation of p21/waf1.…”
Section: Pharmacological Propertiesmentioning
confidence: 99%
“…ROS induced by multiple extracellular and intracellular effects is widely studied as a main cause of oxidative stress. In senescence, a variety of stressors such as endoplasmic reticulum stress and mitochondrial damage can induce the production of ROS, causing downstream DNA damage, increasing expression of molecules such as p53 and p21, and blocking cell cycle [46,75,80]. B-myb expression levels were downregulated in the aortas of aged mouse, and the inhibition of B-myb induced senescence in primary cultured human aortic endothelial cells, which is mediated by ROS production through p53/p21 signal pathway [93].…”
Section: Oxidative Stress-induced Senescencementioning
confidence: 99%
“…An active flavonoid component oroxin A, which is obtained from the traditional Chinese herb Oroxylum indicum (L.) Kurz, increased ER-Tracker Red-positive cell population and upregulated ER stress-related proteins activating transcription factor 4 (ATF4) and binding immunoglobulin protein (GRP78), caused cell cycle arrest at the G2/M phase and induced senescence in human breast cancer cells while p38-specific inhibitor SB203580 blocked ER stress induced senescence [79]. Cristacarpin, a known isoflavonoid isolated from Erythrina suberosa stem bark, enhanced ER stress with increased expressions of GRP-94 and PERK by activation of p38, thereby generating sub-lethal ROS, elevating the expression of p21 waf1 in a p53-independent manner, and reducing the expressions of Cdk-2 and cyclinD1, which in turn caused cellular senescence through G1 phase cell cycle arrest in pancreatic and breast cancer cells [80]. After treatment with flavokawain B, a flavonoid compound, approximately 60% of human glioblastoma multiforme cells became senescent and this result was attributed to ER stress-dependent autophagy, which was regulated by ATF-4/DNA damage inducible transcript 3 (DDIT3)/tribbles pseudokinase 3 (TRIB3)/mTOR signaling pathway [81].…”
Section: Endoplasmic Reticulum (Er) Stress-induced Senescencementioning
confidence: 99%
See 1 more Smart Citation